Предмет: Алгебра, автор: IloveAlmatu

найдите значение выражения ​

Приложения:

Ответы

Автор ответа: MixalicynaBaviria506
0

Объяснение:

 \frac{3 {(x + y)}^{2} }{5(x + y)(x - y)}  \div  \frac{9x(x + y)(x - y)}{10(x + y)(x - y)} =  \frac{3 {(x + y)}^{2} }{5(x + y)(x - y)}  \div  \frac{10(x + y)(x - y)}{9x(x + y)(x - y)}  =  \frac{(5 + 3) \times 2}{3 \times 5(5 - 3)}  =  \frac{16}{30}  =  \frac{8}{15}

Автор ответа: sangers1959
0

Ответ:

Объяснение:

\frac{3x^{2}+3xy+3y^{2}  }{5x^{2} -5y^{2} } :\frac{9x^{3} -9y^{3} }{10x^{2}-10y^{2}  } =\frac{3*(x^{2}+xy+y^{2} ) }{5*(x^{2} -y^{2} )} *\frac{10*(x^{2} -y^{2} ) }{9*(x^{3} -y^{3} )} =\frac{3*(x^{2}+xy+y^{2})*10*(x^{2}  -y^{2} ) }{5*(x^{2} -y^{2} )*9*(x-y)*(x^{2}+xy+y^{2})  } =\\ =\frac{2}{3*(x-y)}=\frac{2}{3*(5-3)}=\frac{2}{3*2} =\frac{1}{3} .

Похожие вопросы
Предмет: Обществознание, автор: gaz1138hjj